Արաբական փոխառություններով կազմված բայերի ձևաիմաստային արտահայտությունները հայրեններում և կաֆաներում - Մհեր Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
Анализ словарного состава айренов и кафов свидетельствует о том, что он пополнялся разными путями, в частности, за счет глаголов, образованных на основе арабских заимствований с помощью присоединения словообразовательных аффиксов, присущих среднеармянскому языку, а также с помощью составных глаголов. The study of the vocabulary of hayrens and kafas indicates that the vocabulary has also been replenished in mixed ways by means of Arabic borrowings and verbs formed as a result of synthetic and analytical types of word-formation in Middle Armenian.
Keywords: Philology; Linguistics; Language and Literature